Antifungal Susceptibility of Dermatophyte Isolates from Patients with Chronic and Recurrent Dermatophytosis - Nikhitha Amin; Manjunath M. Shenoy; Vidya Pai (Indian Dermatology Online Journal)
Background: The widespread occurrence of chronic and recurrent dermatophytosis has significantly affected the quality of life for patients in India and beyond. Identifying the causative dermatophytes and understanding their antifungal susceptibility can aid clinicians in tailoring effective antifungal therapies. Materials and Methods: Patients with chronic and recurrent dermatophytosis were enrolled, and conventional fungal cultures were conducted on skin scrapings. Identified isolates underwent antifungal susceptibility testing using the Clinical and Laboratory Standards Institute broth microdilution method (CLSI M38-A2) for common systemic antifungals, determining the minimum inhibitory concentration (MIC) range and calculating MIC 50 and MIC 90. Results: Sixty samples were tested. Tinea corporis was the most common presentation (66.6%). Trichophyton mentagrophyte species complex was the prevalent species (45, 75%), followed by Trichophyton rubrum (7, 11.7%). In Trichophyton mentagrophytes species complex, MIC range was 8-64 μg/mL for fluconazole, 0.06-0.25 μg/mL for terbinafine, and 0.125-0.5 μg/mL for griseofulvin. For Trichophyton rubrum, the MIC range was 8-64 μg/mL for fluconazole, 0.06-0.25 μg/mL for terbinafine, and 0.125-0.5 μg/mL for griseofulvin. For all species, itraconazole MIC was ≤0.125 μg/mL. Hence, itraconazole and terbinafine had the best MIC range against tested isolates in our study. Limitations: Absence of genotyping of isolate and not compared the results with studies where sequence-based identification to species level was done. Conclusion: In vitro, resistance to itraconazole for any of the four isolated agents was not seen. Terbinafine resistance appears to be an uncommon occurrence in South India. In vitro susceptibility tests shall be regularly done to design the epidemiological cutoff values.